DESA GOMBENGSARI SEBAGAI DESA EKOWISATA DENGAN BRANDING KOPI MENUJU DESA MANDIRI - Dhalia Sutopo; Rachmaniah Mirza Hariastuti; Sri Sedar Marhaeni (Khazanah Pendidikan, 2019)
Gombengsari Village is a cool village, a friendly community, located at the foot of Mount Ijen. Gombengsari Village is located in Kalipuro District, Banyuwangi Regency. The potential of natural resources possessed is enormous, ranging from fertile agricultural land which is good for planting various types of leaf vegetables, fruit vegetables, rice, crops and ornamental plants. There are coffee plantations, Sumber Sweet Suko Park Tourism, Puncak Asmoro tourism, agricultural areas, Bride Cave Bathing Tours, Camping Ground being a part of beautifying Gombengsari Village. From the large natural resource potential of the village of Gombengsari, the level of welfare of the community should be better than other village areas. However, the level of welfare of the people of Gombengsari village is still below average. Community service activities in the village of Gombengsari have been carried out through the Posdaya (Family Empowerment Post) program under the assistance of LPPM PGRI Banyuwangi University. The implementation of Posdaya which was developed has not yet had a maximum impact on improving the economy of the community where there are still several problems that must be solved especially in the sale of coffee yields in the Gombengsari coffee farmer group. With the existence of KKN PPM, it is expected that coffee will become a village brending by solving problems faced by coffee farmers. Keywords: Gombengsari Village, Coffee Branding, Ecotourism Village